2023
DOI: 10.1093/plcell/koad160
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric variation in DNA methylation during domestication and de-domestication of rice

Abstract: Hundreds of plant species have been domesticated to feed human civilization, while some crops have undergone de-domestication into agricultural weeds, threatening global food security. To understand the genetic and epigenetic basis of crop domestication and de-domestication, we generated DNA methylomes from 95 accessions of wild rice (Oryza rufipogon L.), cultivated rice (Oryza sativa L.) and weedy rice (Oryza sativa f. spontanea). We detected a significant decrease in DNA methylation over the course of rice d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 74 publications
1
4
1
Order By: Relevance
“…Cultivated accessions consistently exhibit significantly higher global levels of DNA methylation across all sequence contexts and all genomic features. These observations, are in contradiction with previous studies showing that domestication induces a significant decrease in DNA methylation in rice [ 29 ] and tomato [ 30 ]. This is perhaps explained by the differences in the type of propagation used during the domestication of each species (i.e., vegetative vs. sexual propagation), which could have resulted in diametrically opposed domestication epigenetic syndromes [ 2 , 6 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Cultivated accessions consistently exhibit significantly higher global levels of DNA methylation across all sequence contexts and all genomic features. These observations, are in contradiction with previous studies showing that domestication induces a significant decrease in DNA methylation in rice [ 29 ] and tomato [ 30 ]. This is perhaps explained by the differences in the type of propagation used during the domestication of each species (i.e., vegetative vs. sexual propagation), which could have resulted in diametrically opposed domestication epigenetic syndromes [ 2 , 6 ].…”
Section: Discussioncontrasting
confidence: 99%
“…A reduction that is reversed in the resynthesized hexaploid wheat [ 27 ]. More recently, detailed analysis of DNA methylation in rice [ 29 ] and tomato [ 30 ] has shown that domesticated cultivars present lower levels of DNA methylation than their wild counterparts. Moreover, multiple studies have shown that differentially methylated regions associated to domestication overlap with genes linked to traits known to be under selection during domestication of soybean [ 31 ], tomato [ 30 ], maize [ 32 ], and cotton [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, this approach primarily focuses on DNA variations within coding regions or proximal promoter regions. It is essential to recognize that variations in DNA methylation status, rather than the sequence itself, can also be associated with traits in crop plants [ 80 ], such as domestication in rice [ 81 ]. For instance, a naturally occurring DNA methylation variation in the promoter of Colorless non-ripening (Cnr) locus is associated with the fruit ripening in tomato [ 82 ], demonstrating the significance of DNA methylation in trait association.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…DNA methylation influences chromatin accessibility and histone modifications, which in turn controls the expression of nearby and distant genes throughout the domestication process of rice. Domesticated rice experiences a decrease in the DNA methylation linked to stress tolerance, but weedy rice, which can withstand more severe stress, may show an increase in this link [143]. The drought response regulatory network of Fragaria nilgerrensis was revealed by means of a thorough examination of gene expression profiles, whole-genome DNA methylation maps, and physiological parameters at four distinct time points under drought stress treatment [144].…”
Section: Dna Methylation and Plant Stressmentioning
confidence: 99%